Industrial Color Physics - Klein, Georg A.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This unique book starts with a short historical overview of the development of the theories of color vision and applications of industrial color physics. The three dominant factors producing color - light source, color sample, and observer - are described in detail. The standardized color spaces are shown and related color values are applied to characteristic color qualities of absorption as well as of effect colorants. The fundamentals of spectrometric and colorimetric measuring techniques together with specific applications are described. Theoretical models for radiative transfer in transparent, translucent, and opaque layers are detailed; the two, three, and multi-flux approximations are presented for the first time in a coherent formalism. These methods constitute the fundamentals not only for the important classical methods, but also modern methods of recipe prediction applicable to all known colorants. The text is supplied with 52 tables, more than 200 partially colored illustrations, an appendix, and a detailed bibliography. This work is recommended particularly for physicists, chemists, and engineers in color industry and related fields of research, development, production, and processing; this work provides the fundamentals over the widespread physical properties and applications of absorption and effect colorants and is suitable for both the beginner and experienced developer. The author, Georg A. Klein, was awarded his Ph. D. in polymer physics from the University of Mainz, Germany. After several years of R&D in the chemical industry, he became a professor for physics, color physics, and technology of polymers at the University of Applied Sciences in Stuttgart. His extensive decades-long experience in color physics and color technology in Germany and abroad is condensed in the present book.
Introduction -- Light sources, types of colorants, observer -- Optical radiation sources and interaction of light -- Absorbing colorants -- Effect pigments -- Observer -- References -- Systems of standardized tristimulus values, color qualities, chroma of effect pigments -- Systems of standardized tristimulus values -- Color difference metrics and color tolerances -- Color inconstancy and metamerism -- Specific qualities of colorants -- Colorimetry of effect pigments -- References -- Measuring Colors -- Measuring of reflecting and transmitting materials -- Measuring geometries -- Uncertainties of spectral color measurement -- References -- Theories of radiative transfer -- Fundamentals -- Directional two-flux approximation -- Theory of Kubelka and Munk -- Three-flux approximation -- Approximation of radiative transfer by multi-flux theory -- References -- Recipe prediction -- Calibration samples -- Strategies for recipe prediction -- Realization of recipes -- References -- Appendix -- Non-colored applications of effect pigments -- Chromatic adaption transform CAT02 -- Two-flux approximations -- References in alphabetic order, figure sources -- Subject index.
Keywords: Physics; Chemical engineering; Optics; Electrodynamics; Optoelectronics; Plasmons (Physics).; Microwaves; Optical engineering; Physics; Optics and Electrodynamics; Optics, Optoelectronics, Plasmonics and Optical Devices; Industrial Chemistry/Chemical Engineering; Microwaves, RF and Optical Engineering; Electronic books